Taxonomic revision of the genus Tarmia Lindsey, 1925 stat. rev. (Hesperiidae: Hesperiinae: Hesperiini: Moncina) with the description of a new species from the Andes - de Medeiros, Adalberto Dantas; Warren, Andrew D.; Dolibaina, Diego Rodrigo; Carneiro, Eduardo; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2019)
The genus Tarmia Lindsey, 1925, long considered a junior synonym of Phanes Godman, 1901, is here revised and its status is revalidated based on morphological evidence. Two Andean species are included in Tarmia: the type species, T. monastica Lindsey, 1925 comb. rev., and a new species herein described, Tarmia greeneyi A. Warren, Medeiros, Dolibaina & O. Mielke sp. nov., from Ecuador, Peru and Bolivia. The male’s symmetrical valvae and aedeagus with a twisted median portion, and the very wide ductus bursae of the female genitalia support Tarmia as valid genus apart of Phanes. Illustrations of the main diagnostic characters of both sexes and a distribution map are provided for the species of Tarmia.